2018
DOI: 10.1002/chem.201800172
|View full text |Cite
|
Sign up to set email alerts
|

12‐Vertex Zwitterionic Bis‐phosphonium‐nido‐carborates through Ring‐Opening Reactions of 1,2‐Diphosphetanes

Abstract: Carborane-substituted 1,2-diphosphetanes (Ia,b) react with elemental lithium in THF with cleavage of the P-P bond to give a deep red solution from which, in the case of Ia, red crystals of a lithiated intermediate, [{1-Li(THF)PtBu-6-PtBu-4,1,6-closo-Li(THF)C B H }{Li(THF) }] ⋅2 THF (2 a), are obtained. The compound is dimeric, C -symmetric and contains six lithium and four phosphorus atoms. Two lithium atoms cap the six-membered C B faces, resulting in two 13-vertex closo-clusters (according to Wade's rules) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The Hey-Hawkins group reported a related carboranyl diphosphetane that displays similar oxidative addition-type reactivity in the presence of MeI. 69 The synthesized carboranyl diphosphetane undergoes P–P bond activation and cluster opening upon reduction with lithium metal. The reaction of the resulting Li intermediate with excess MeI induces the methylation of both phosphorus centers, generating a zwitterionic bis-phosphonium- nido -carborane (Fig.…”
Section: Bond Activations By Carboranyl Diphosphinesmentioning
confidence: 99%
“…The Hey-Hawkins group reported a related carboranyl diphosphetane that displays similar oxidative addition-type reactivity in the presence of MeI. 69 The synthesized carboranyl diphosphetane undergoes P–P bond activation and cluster opening upon reduction with lithium metal. The reaction of the resulting Li intermediate with excess MeI induces the methylation of both phosphorus centers, generating a zwitterionic bis-phosphonium- nido -carborane (Fig.…”
Section: Bond Activations By Carboranyl Diphosphinesmentioning
confidence: 99%
“…The carbon atoms of ortho -C 2 B 10 H 12 form single bonds to exohedral substituents, and π-back-donation from those groups to the cluster can increase the exohedral bond order and weaken the intracluster C–C bond. , Recently, there was a report of opening of the ortho -{C 2 B 10 } cage upon the reaction of carboranyl diphosphines with HCl, leading to the formation of a zwitterionic nido -cluster that contains two phosphonium centers (Scheme I) . Albeit complicated by side reactions and only partial conversion, similar reactivity has been observed between a carboranyl diphosphine and methyl iodide: the phosphorus centers become methylated and the carborane cage opens . Concomitant formation of I 2 has been proposed as a source of electrons for the cluster reduction (Scheme J).…”
mentioning
confidence: 99%
“…28 and only partial conversion, similar reactivity has been observed between a carboranyl diphosphine and methyl iodide: the phosphorus centers become methylated and the carborane cage opens. 29 Concomitant formation of I 2 has been proposed as a source of electrons for the cluster reduction (Scheme 1J). Conceptually, carboranyl diphosphines represent a metalfree cluster-containing molecular framework that combines two important features normally reserved for transition metals: the simultaneous ability to accept electrons to cycle through two-electron redox states and the ability to donate electrons through Lewis basic binding sites (Scheme 1K).…”
mentioning
confidence: 99%
“…A single crystal X-ray diffraction study revealed the structure of P­(H)­( i Pr 2 )­P­(CHCPh)­( t Bu 2 )­(C 2 B 10 H 9 ) ( 2 ) (Figure ) and confirmed the carborane cage is an open 12-vertex nido -cluster, which is reduced by two electrons. The cluster is C 2 -symmetric, giving rise to two enantiomers of 2 that co-crystallized as a racemate. The P­( i Pr 2 ) group is protonated, and the P­( t Bu 2 ) group is converted to an alkenylphosphonium center through the attachment of phenylacetylene.…”
Section: Resultsmentioning
confidence: 99%